Periodontitis Is Associated With Heart Failure: A Population-Based Study (NHANES III) - Yan Yan; Min Mao; Yanqin Li; Yongji Chen; Hedong Yu; Wen‐Zhong Xie; Qiao Huang; Wei‐Dong Leng; Jie Xiong (2022)
Objectives: The aim of this study was to investigate the relationship between periodontitis and heart failure using the Third National Health and Nutrition Examination Survey (NHANES III). Methods: Participants who had received a periodontal examination were included and investigated for the occurrence of heart failure. The included participants were divided into no/mild periodontitis and moderate/severe periodontitis groups according to their periodontal status. Weighted prevalence of heart failure was calculated, and weighted logistic regressions models were used to explore the association between periodontitis and heart failure. Possible influencing factors were then explored through subgroup analysis. Results: Compared with that of the no/mild periodontitis group, the incidence of heart failure in participants with moderate/severe periodontitis was 5.72 times higher (95% CI: 3.76-8.72, p < 0.001). After adjusting for gender, age, race, body mass index, poverty income ratio, education, marital status, smoking status, drinking status, hypertension, diabetes, stroke, and asthma, the results showed that the incidence of heart failure in the moderate/severe group was 3.03 times higher (95% CI: 1.29-7.13, p = 0.012). Subgroup analysis showed that criteria, namely, male, 40-60 years old, non-Hispanic white, body mass index >30, poverty income ratio ≥1, not more than 12 years of education, currently drinking, stroke but no diabetes, or asthma supported moderate/severe periodontitis as a risk factor for heart failure (p < 0.05). Conclusion: According to data from this nationally representative sample from the United States, periodontitis is associated with an increased risk of heart failure.